Epidemiologia do traumatismo craniencefálico urbano em Hospital Universitário de São José do Rio Preto - Filipe, Fernando Manuel Rana (2011)
Traumatic brain injury is the leading cause of disability, morbidity and mortality in people and has become a very important public health issue with high socioeconomic costs. Aim: To evaluate traumatic brain injuries in an urban area in respect to gender, age, occupation and schooling of the victim, the etiology of the injury, duration of hospitalization, evolution and the influence of changes in the road traffic laws on the occurrence of traumatic brain injuries. Patients and Methods: A total of 258 patients admitted to Hospital de Base as victims of brain injuries inside the urban area of São José do Rio Preto from 2005 to 2008 were analyzed. Results: Of this total, 216 were men (83.7%) with a mean age of 44.8 years (range: 4-89 years) and 42 were women (16.3%) with a mean age of 53.3 years (range: 13-96 years). Falls (34.5%) and motorcycle accidents (21.7%) were the most frequent etiologies. Mean hospitalization was 6.7 days. In general, victims were service sector workers (51.1%) and had only completed junior school (56.2%). The mortality rate among individuals who suffered traumatic brain injuries was 26.7%. A non-statistically significant drop (about 50%) in the number of traumatic brain injuries was recorded in the first half of 2008, which coincided with the introduction of tougher road traffic laws that increased punishment for drink drivers and decreased the legal blood alcoholic limit. Conclusion: Traumatic brain injuries predominantly involve men with a lower age than women. Falls are the most frequent cause in aged people, followed by motorcycle accidents in young individuals. Service sector workers are more likely to suffer traumatic brain x injuries than other manual workers. The recent change in the drink driver laws did not influence the occurrence of traumatic brain injuries.